Evaluating Bees Algorithm for Sequence-based T-way Testing Test Data Generation - M. H., Mohamed Zabil; Kamal Z., Zamli; K. C., Lim (Informatics Publishing Limited, 2018)
T-way testing is a testing technique that is used to detect faults due to parameter interactions or software configurations. In order to perform t-way testing, software testers need to prepare the test data. For a system with many configuration parameters, the test data could lead to combinatorial explosion problem, since all possible parameter combinations need to be considered. Therefore, test data generation for t-way testing need to be optimized. Many t-way test data generation strategies have been proposed in the literature to generate optimized t-way test data. However, very few strategies have been proposed for sequence-based t-way. This paper presents statistical analysis on the performance of Bees Algorithm against the other sequence t-way strategies, in order to generate test cases.